Bringing the family logic in from duality to plurality in social enterprises - Drencheva, Andreana; Wee Chan Au (2023)
Social enterprises combine activities, processes, structures, and meanings associated with multiple institutional logics that may pose conflicting goals, norms, values, and practices. This in-depth multi-source case study of an ecological social enterprise in Malaysia reveals how the enactment of the family logic interacts with the market and ecological logics not only in conflicting but also in synergetic ways. By drawing attention to the institutional logic of the family in social entrepreneurship, this study highlights the heterogeneity of social enterprises. The findings have implications for research with social enterprises and family-owned firms in relation to the ethical obligations of these organizations and the interactions of multiple logics.
Keywords: Family logic; Family-owned firm; Hybrid organizing; Social Enterprise; Social Entrepreneurship; Aufsatz in Zeitschrift